Host cell recognition by the henipaviruses: Crystal structures of the Nipah G attachment glycoprotein and its complex with ephrin-B3 - Xu, Kai (National Academy of Sciences, 2008)
Nipah virus (NiV) and Hendra virus are the type species of the highly pathogenic paramyxovirus genus Henipavirus, which can cause severe respiratory disease and fatal encephalitis infections in humans, with case fatality rates approaching 75%. NiV contains two envelope glycoproteins, the receptor-binding G glycoprotein (NiV-G) that facilitates attachment to host cells and the fusion (F) glycoprotein that mediates membrane merger. The henipavirus G glycoproteins lack both hemagglutinating and neuraminidase activities and, instead, engage the highly conserved ephrin-B2 and ephrin-B3 cell surface proteins as their entry receptors. Here, we report the crystal structures of the NiV-G both in its receptor-unbound state and in complex with ephrin-B3, providing, to our knowledge, the first view of a paramyxovirus attachment complex in which a cellular protein is used as the virus receptor. Complex formation generates an extensive protein–protein interface around a protruding ephrin loop, which is inserted in the central cavity of the NiV-G β-propeller. Analysis of the structural data reveals the molecular basis for the highly specific interactions of the henipavirus G glycoproteins with only two members (ephrin-B2 and ephrin-B3) of the very large ephrin family and suggests how they mediate in a unique fashion both cell attachment and the initiation of membrane fusion during the virus infection processes. The structures further suggest that the NiV-G/ephrin interactions can be effectively targeted to disrupt viral entry and provide the foundation for structure-based antiviral drug design.